Armed conflict and displacement the protection of refugees and displaced persons under international humanitarian law - Jacques, Melanie (Cambridge studies in international and comparative law (Cambridge, England : 1996), 2012)
A detailed analysis of contemporary issues relating to international humanitarian law and its interplay with war migrants.